Health of the War Worker (London : Labour Research Department)
1942-04 1942 1940s 44 pages So much for keeping the place warm. Sometimes this need to keep up the temperature to 60° is given as an excuse to exclude the entry of fresh air, but this must not be accepted. If the incoming air is too cold, it should be warmed, quite a possible and practical arrangement and much cheaper than a high rate of sickness from workers breathing too many of their neighbours' germs as happens in atmospheres that are not changed frequently enough. However, besides getting too cold, factories may get too hot. Too hot an atmosphere, especially if it is combined with a high degree of humidity, may be very fatiguing. The discomfort is greatly lessened if the air is kept moving. Fans are very plentifully distributed in West End clubs, but are much too rare in factories, though they are easy to install. Workers who want to feel comfortable in hot shops in order to get on with their jobs should certainly ask for them, and also for provision of a saline drink. Dampness The Factories Act, Par 1. 6, requires that "where any process is carried on which renders the floor liable to be wet ... effective means shall be provided for draining off the wet." This only caters for excessive wetting, but wherever it is at all possible, efforts should be made to keep premises properly dry. The nature of the process may sometimes make this impossible, and such processes are covered by special regulations under Section 52 of the Act. Spacing It is extremely important from the health point of view that people should not work together in too confined a space. Under the Factories Act, a factory in operation before July, 1937, is deemed overcrowded if there are not 250 cu. ft. of air space per person. This is not sufficient for present-day standards and a factory coming into use for the first time since July, 1937, must provide 400 cu. ft. of air space per person. To arrive at the number of cubic feet per person, it is necessary to multiply the width by the breadth of the room and then by the height, not taking into consideration any height over 14 feet. The *It has been shown that men employed in blast-furnaces, rolling mills, and puddling furnaces show a substantial seasonal fall in output during the hot weather (Industrial Fatigue Research Board, Report No. 5, 1920), while observations made on 138 colliers under varying conditions of heat and ventilation showed output under the worst conditions 41 per cent less than under the best (I.F.R.B., Report No. 39, 1927). 4 21/2049